Timely Reporting and Interactive Visualization of Animal Health and Slaughterhouse Surveillance Data in Switzerland - Muellner, Ulrich J.; Vial, Flavie; Wohlfender, Franziska; Hadorn, Daniela; Reist, Martin; Muellner, Petra (Frontiers in Veterinary Science, 2015)
The reporting of outputs from health surveillance systems should be done in a near real-time and interactive manner in order to provide decision makers with powerful means to identify, assess and manage health hazards as early and efficiently as possible. While this is currently rarely the case in veterinary public health surveillance, reporting tools do exist for the visual exploration and interactive interrogation of health data. In this work, we used tools freely available from the Google Maps and Charts library to develop a web application reporting health-related data derived from slaughterhouse surveillance and from a newly established web-based equine surveillance system in Switzerland. Both sets of tools allowed entry-level usage without or with minimal programming skills while being flexible enough to cater for more complex scenarios for users with greater programming skills. In particular, interfaces linking statistical softwares and Google tools provide additional analytical functionality (such as algorithms for the detection of unusually high case occurrences) for inclusion in the reporting process. We show that such powerful approaches could improve timely dissemination and communication of technical information to decision-makers and other stakeholders and could foster the early-warning capacity of animal health surveillance systems.